2015
DOI: 10.3390/molecules201219860
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry Approach for Synthesis of Effective Anticancer Palladium Nanoparticles

Abstract: Abstract:The purpose of this study was to design and synthesize Palladium nanoparticles (PdNPs) using an environmentally friendly approach and evaluate the in vitro efficacy of PdNPs in human ovarian cancer A2780 cells. Ultraviolet-Visible (UV-Vis) spectroscopy was used to monitor the conversion of Pd(II) ions to Pd(0)NPs. X-ray diffraction (XRD) revealed the crystallinity of the as-synthesized PdNPs and Fourier transform infrared spectroscopy (FTIR) further confirmed the role of the leaf extract of Evolvulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 98 publications
8
108
0
Order By: Relevance
“…It is proposed that the high cytotoxicity of Pd@W.tea NPs to the cancer cell line is due to the presence of Pd, which interacts physicochemically with the functional groups of cellular proteins, nitrogen bases, and phosphate groups of the DNA, 36 thus causing cell death. Moreover, previous studies showed that Pd causes production of free radical, 37 lactate dehydrogenase leakage, 15 and cell-cycle disturbances 38 that could be among mechanisms of the anticancer effects of Pd@W.tea NPs.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that the high cytotoxicity of Pd@W.tea NPs to the cancer cell line is due to the presence of Pd, which interacts physicochemically with the functional groups of cellular proteins, nitrogen bases, and phosphate groups of the DNA, 36 thus causing cell death. Moreover, previous studies showed that Pd causes production of free radical, 37 lactate dehydrogenase leakage, 15 and cell-cycle disturbances 38 that could be among mechanisms of the anticancer effects of Pd@W.tea NPs.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…12,14 Plant-derived PdNPs seem to have potential for application in cancer therapy because these compounds are also toxic to cancer cells. 15,16 In this study, we demonstrated a simple one-step green process to synthesize PdNPs using Camellia sinensis (white tea [W.tea]) extract from unfermented young tea leaves or unopened buds. 17 The white tea extract has been used as an efficient reducing and capping agent.…”
Section: Introductionmentioning
confidence: 99%
“…21 In a typical experiment, the reaction mixture was prepared by suspending 10 mL of RPE (4 μM) in 10 mL of sterile distilled water and this was mixed well for 5 min and then added to 90 mL of 1 mM PdCl 2 solution in a 250 mL round bottom flask, which was mounted with a cooling condenser and a magnetic stir bar. The mixture was stirred for 2 h at 60°C with constant stirring.…”
Section: Synthesis and Characterization Of Pdnpsmentioning
confidence: 99%
“…21 Spectra of the synthesized PdNPs were recorded using a ultraviolet (UV)-visible spectrophotometer from 300 nm to 600 nm. X-ray diffraction (XRD) analyses were performed using a Bruker D8 Discover X-ray diffractometer (Bruker AXS GmBH, Karlsruhe, Germany).…”
Section: Synthesis and Characterization Of Pdnpsmentioning
confidence: 99%
See 1 more Smart Citation